(untitled) (Sciences & Technologie. B, Sciences de l’ingénieur, 2007)
A special finite element based on Reissner’s mixed variational principle has been presented to study interfacial cracks in bimaterials. The present element is a 7-node two dimensional mixed finite element with 5 displacement nodes and 2 stress nodes. The mixed interface finite element ensures the continuity of stress and displacement vectors at the interface on the coherent part and the discontinuity of this one on the cracked part. This interface element was associated with the virtual crack extension method to evaluate the energy release rates using only one meshing by finite elements. Results obtained from the present mixed interface element have been shown to be in good agreement with the analytical solutions